You should find the equation of the line that passes through `(0,-2)` and it is parallel to the line `y-3=3(x+1), ` such that:

`y - (-2) = m(x - 0)`

You need to remember that the slopes of two parallel lines are equal, hence, you may find the slope m evaluating the slope of the line `y-3=3(x+1),` thus, you need to convert the given form into slope intercept form, such that:

`y-3=3(x+1) => y = 3x + 3 + 3 =>y = 3x+ 6`

Notice that the slope o parallel line is `m = 3` , hence, you may substitute 3 for m in equation `y - (-2) = m(x - 0), ` such that:

`y+ 2= 3x`

You need to convert the point slope form of the equation of parallel line, in standard form, hence, you need to move all terms to the left side, such that:

`-3x + y + 2 = 0 => 3x - y - 2 = 0`

**Hence, evaluating the standard form of equation of the line passing through `(0,-2)` and parallel to the line `y-3=3(x+1), ` yields `3x - y - 2 = 0.` **